AGO2-RIP-Seq reveals miR-34/miR-449 cluster targetome in sinonasal cancers. - Marco Tomasetti; Federica Monaco; Corrado Rubini; Marzia Rossato; Concetta De Quattro; Cristina Beltrami; Giacomo Sollini; Ernesto Pasquini; Monica Amati; Gaia Goteri; Lory Santarelli; Massimo Re (PLoS ONE, 2024)
Sinonasal tumours are heterogeneous malignancies, presenting different histological features and clinical behaviour. Many studies emphasize the role of specific miRNA in the development and progression of cancer, and their expression profiles could be used as prognostic biomarkers to predict the survival. Recently, using the next-generation sequencing (NGS)-based miRNome analysis the miR-34/miR-449 cluster was identified as miRNA superfamily involved in the pathogenesis of sinonasal cancers (SNCs). In the present study, we established an Argonaute-2 (AGO2): mRNA immunoprecipitation followed by high-throughput sequencing to analyse the regulatory role of miR-34/miR-449 in SNCs. Using this approach, we identified direct target genes (targetome), which were involved in regulation of RNA-DNA metabolic, transcript and epigenetic processes. In particular, the STK3, C9orf78 and STRN3 genes were the direct targets of both miR-34c and miR-449a, and their regulation are predictive of tumour progression. This study provides the first evidence that miR-34/miR-449 and their targets are deregulated in SNCs and could be proposed as valuable prognostic biomarkers.